Coated particles, resin composition, connecting structure, and method for manufacturing coated particles
Patent Information
- Application Number
- JP2022538343
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-11
- Filing Date
- 2022-06-10
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2042-06-10
AI Technical Summary
【0021】 本発明に係る被覆粒子は、絶縁性粒子付き導電性粒子と、フッ素を含む有機化合物とを備え、上記絶縁性粒子付き導電性粒子が、導電性粒子と、上記導電性粒子の表面上に配置された複数の絶縁性粒子とを有する。本発明に係る被覆粒子では、上記導電性粒子が、基材粒子と、上記基材粒子の表面上に配置された導電部とを有する。本発明に係る被覆粒子では、上記フッ素を含む有機化合物が、上記絶縁性粒子付き導電性粒子の表面の少なくとも一部を被覆している。本発明に係る被覆粒子では、上記の構成が備えられているので、粒子の凝集を抑制することができ、電極間を電気的に接続した場合に、導通信頼性を高めることができ、かつ、絶縁信頼性を高めることができる。
Smart Images

Figure 0007917442000003 
Figure 0007917442000004 
Figure 0007917442000005
Abstract
Description
Technical Field
[0001] The present invention relates to coated particles using conductive particles with insulating particles. The present invention also relates to a resin composition and a connection structure using the coated particles. Background Art
[0002] Anisotropic conductive materials such as anisotropic conductive paste and anisotropic conductive film are widely known. In such an anisotropic conductive material, conductive particles are dispersed in a binder resin.
[0003] The above anisotropic conductive material is used to obtain various connection structures. Examples of connection using the anisotropic conductive material include connection between a flexible printed circuit board and a glass substrate (FOG (Film on Glass)), connection between a semiconductor chip and a flexible printed circuit board (COF (Chip on Film)), connection between a semiconductor chip and a glass substrate (COG (Chip on Glass)), and connection between a flexible printed circuit board and a glass epoxy substrate (FOB (Film on Board)).
[0004] As the above conductive particles, conductive particles with insulating particles in which insulating particles are arranged on the surface of conductive particles are sometimes used. In the above conductive particles with insulating particles, a coating portion may be formed on the surface to suppress detachment of the insulating particles from the conductive particle body before conductive connection.
[0005] Conductive particles with insulating particles having a coating portion on the surface are disclosed in Patent Documents 1 and 2 below.
[0006] Patent Document 1 discloses conductive particles with insulating particles (coated particles) comprising a conductive particle body with insulating particles and a coating covering the surface of the conductive particle body with insulating particles. The conductive particle body with insulating particles comprises a conductive particle having a conductive portion at least on its surface and a plurality of insulating particles arranged on the surface of the conductive particle. In the conductive particles with insulating particles, the coating has a first coating portion covering the conductive particle and a second coating portion covering the surface of the insulating particle, and the thickness of the first coating portion is 1 / 2 or less of the average particle diameter of the insulating particle. Patent Document 1 states that it is preferable that the coating is formed of a compound having an alkyl group having 6 to 22 carbon atoms.
[0007] Furthermore, Patent Document 2 discloses water-repellent conductive particles (coated particles) comprising base particles having a surface made of a conductive metal and insulating protrusions (coatings) present on the surface of the base particles. At least one of the base particles and the protrusions is chemically bonded to a compound having hydrophobic groups, and in the water-repellent conductive particles, the surface-to-surface ratio represented by a specific formula (1) is 0.05 to 0.17. Patent Document 2 states that silicone compounds are preferred as the compound having hydrophobic groups. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Japanese Patent Publication No. 2013-175453 [Patent Document 2] Japanese Patent Publication No. 2013-105537 [Overview of the project] [Problems that the invention aims to solve]
[0009] As described in Patent Document 1, coated particles in which the coating portion is formed by a compound having an alkyl group have a problem in that the hydrophobicity of the coating portion is insufficient, making the coated particles prone to aggregation.
[0010] As described in Patent Document 2, coated particles whose surfaces are coated with a silicone compound have low electron repulsion, making it difficult to disperse the coated particles and thus difficult to sufficiently suppress aggregation of the coated particles.
[0011] Furthermore, when an anisotropic conductive material is made using coated particles that have aggregated and a binder resin, the particles may not be uniformly distributed between the upper and lower electrodes that are to be connected after coating with the anisotropic conductive material, making it difficult to sufficiently improve conductivity reliability. In addition, the presence of aggregated particles can easily cause short circuits between laterally adjacent electrodes that should not be connected, resulting in low insulation reliability between laterally adjacent electrodes.
[0012] The object of the present invention is to provide coated particles that can suppress particle aggregation, improve conductivity reliability when electrodes are electrically connected, and improve insulation reliability. Another object of the present invention is to provide a resin composition and a connecting structure using the above coated particles. [Means for solving the problem]
[0013] A broad aspect of the present invention provides a coated particle comprising a conductive particle with insulating particles and an organic compound containing fluorine, wherein the conductive particle with insulating particles comprises a conductive particle and a plurality of insulating particles disposed on the surface of the conductive particle, the conductive particle comprises a base particle and a conductive portion disposed on the surface of the base particle, and the organic compound containing fluorine coats at least a portion of the surface of the conductive particle with insulating particles.
[0014] In a specific aspect of the coated particles according to the present invention, the fluorine-containing organic compound is polyvinylidene fluoride, a perfluoroalkyl compound, or a polyfluoroalkyl compound.
[0015] In a particular aspect of the coated particles according to the present invention, the fluorine-containing organic compound coats at least a portion of the surface of the conductive portion and at least a portion of the surface of the insulating particles.
[0016] In a particular aspect of the coated particles according to the present invention, the insulating particles are resin particles.
[0017] In a particular surface of the coated particles according to the present invention, the area of the portion covered by the insulating particles is 30% or more and 70% or less of the total surface area of the conductive portion.
[0018] In a broader sense, the present invention provides a resin composition comprising the above-mentioned coated particles and a binder resin.
[0019] In a specific aspect of the resin composition according to the present invention, the proportion of non-aggregated coated particles out of 100% of the total number of coated particles in the binder resin is 80% or more.
[0020] In a broader sense, the present invention provides a connection structure comprising a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connecting portion connecting the first connection target member and the second connection target member, wherein the material of the connecting portion includes the above-mentioned coating particles, and the first electrode and the second electrode are electrically connected by the conductive particles. [Effects of the Invention]
[0021] The coated particles according to the present invention comprise conductive particles with insulating particles and a fluorine-containing organic compound, wherein the conductive particles with insulating particles include conductive particles and a plurality of insulating particles arranged on the surface of the conductive particles. In the coated particles according to the present invention, the conductive particles include base material particles and a conductive portion arranged on the surface of the base material particles. In the coated particles according to the present invention, the fluorine-containing organic compound covers at least a part of the surface of the conductive particles with insulating particles. Since the coated particles according to the present invention have the above configuration, aggregation of the particles can be suppressed, and when electrodes are electrically connected to each other, conduction reliability can be improved, and insulation reliability can be improved. [Brief Description of the Drawings]
[0022] [Figure 1] Figure 1 is a cross-sectional view showing coated particles according to a first embodiment of the present invention. [Figure 2] Figure 2 is a cross-sectional view showing coated particles according to a second embodiment of the present invention. [Figure 3] Figure 3 is a cross-sectional view showing coated particles according to a third embodiment of the present invention. [Figure 4] Figure 4 is a cross-sectional view schematically showing a connection structure using coated particles according to the first embodiment of the present invention. [Mode for Carrying Out the Invention]
[0023] Hereinafter, the present invention will be described in detail.
[0024] (Coated particles) The coated particles according to the present invention comprise conductive particles with insulating particles and a fluorine-containing organic compound. In the coated particles according to the present invention, the conductive particles with insulating particles include conductive particles and a plurality of insulating particles arranged on the surface of the conductive particles. In the coated particles according to the present invention, the conductive particles include base material particles and a conductive portion arranged on the surface of the base material particles. In the coated particles according to the present invention, the fluorine-containing organic compound covers at least a part of the surface of the conductive particles with insulating particles.
[0025] Since the coated particles according to the present invention have the above configuration, particle aggregation can be suppressed, and when electrodes are electrically connected, conductivity reliability can be improved and insulation reliability can be improved.
[0026] Specific embodiments of the present invention will be described below with reference to the drawings. Note that parts that differ between Figure 1 and the later drawings are interchangeable. Also, for illustrative purposes, the size and thickness of each component shown in Figure 1 and the later drawings may differ from the actual size and thickness.
[0027] Figure 1 is a cross-sectional view showing coated particles according to the first embodiment of the present invention.
[0028] The coated particle 1 shown in Figure 1 comprises conductive particles 2 with insulating particles and an organic compound 3 containing fluorine. In the coated particle 1, the conductive particles 2 with insulating particles have conductive particles 11 and a plurality of insulating particles 12 arranged on the surface of the conductive particles 11. In the coated particle 1, the conductive particles 11 have a base particle 21 and a conductive portion 22 arranged on the surface of the base particle 21.
[0029] In coated particle 1, a fluorine-containing organic compound 3 coats the surface of the conductive particle 2 with insulating particles. In coated particle 1, the fluorine-containing organic compound 3 coats the surface of the conductive particle 11 (surface of the conductive part 22) and the surface of the insulating particle 12. In coated particle 1, the fluorine-containing organic compound 3 is arranged on the surface of the conductive particle 11 (surface of the conductive part 22) and the surface of the insulating particle 12, and is in contact with the conductive particle 11 (conductive part 22) and the insulating particle 12.
[0030] In coated particle 1, insulating particles 12 are arranged on the surface of conductive particles 11. In coated particle 1, insulating particles 12 are arranged on the surface of conductive portion 22 and are in contact with conductive portion 22.
[0031] The conductive portion 22 covers the surface of the base particle 21. In the conductive particle 11, the surface of the base particle 21 is covered by the conductive portion 22. The conductive particle 11 has the conductive portion 22 on its surface.
[0032] In coated particle 1, the conductive portion 22 is a conductive layer. The conductive portion 22 is a single-layer conductive layer. In the conductive particle, the conductive portion may cover the entire surface of the base particle, or it may cover a part of the surface of the base particle.
[0033] Coated particles 1 can be obtained, for example, by dipping conductive particles 2 (conductive particles 11 with insulating particles 12 attached) with a dispersion of fluorine-containing organic compounds, before the fluorine-containing organic compound 3 is placed on them, into a dispersion of fluorine-containing organic compounds to form the fluorine-containing organic compound 3. Coated particles 1A and 1B, described later, can also be obtained in the same manner as coated particles 1.
[0034] Figure 2 is a cross-sectional view showing coated particles according to a second embodiment of the present invention.
[0035] The coated particle 1A shown in Figure 2 comprises a conductive particle 2A with insulating particles and an organic compound 3A containing fluorine. In the coated particle 1A, the conductive particle 2A with insulating particles has a conductive particle 11A and a plurality of insulating particles 12A arranged on the surface of the conductive particle 11A. In the coated particle 1A, the conductive particle 11A has a base particle 21A and a conductive portion 22A arranged on the surface of the base particle 21A.
[0036] In coated particle 1A, a fluorine-containing organic compound 3A coats the surface of the conductive particle 2A with insulating particles. In coated particle 1A, the fluorine-containing organic compound 3A coats the surface of the conductive particle 11A (the surface of the conductive part 22A) and the surface of the insulating particle 12A. In coated particle 1A, the fluorine-containing organic compound 3A is arranged on the surface of the conductive particle 11A (the surface of the conductive part 22A) and on the surface of the insulating particle 12A, and is in contact with the conductive particle 11A (conductive part 22A) and the insulating particle 12A.
[0037] In coated particle 1A, insulating particles 12A are arranged on the surface of conductive particles 11A. In coated particle 1A, insulating particles 12A are arranged on the surface of conductive portion 22A and are in contact with conductive portion 22A.
[0038] In coated particle 1A, the conductive portion 22A is a two-layer conductive layer. The conductive portion 22A comprises a first conductive portion 22AA and a second conductive portion 22AB. In the conductive portion 22A, the first conductive portion 22AA is laminated on the surface of the base particle 21A, and the second conductive portion 22AB is laminated on the surface of the first conductive portion 22AA.
[0039] The conductive portion of coated particle 1 and coated particle 1A has a different structure. The conductive portion may be a single conductive layer or a multilayer conductive layer.
[0040] Figure 3 is a cross-sectional view showing coated particles according to a third embodiment of the present invention.
[0041] The coated particle 1B shown in Figure 3 comprises a conductive particle 2B with insulating particles and an organic compound 3B containing fluorine. In the coated particle 1B, the conductive particle 2B with insulating particles has a conductive particle 11B and a plurality of insulating particles 12B arranged on the surface of the conductive particle 11B. In the coated particle 1B, the conductive particle 11B has a base particle 21B, a conductive portion 22B arranged on the surface of the base particle 21B, and a plurality of core materials 23B arranged on the surface of the base particle 21B.
[0042] In coated particle 1B, a fluorine-containing organic compound 3B coats the surface of the conductive particle 2B with insulating particles. In coated particle 1B, the fluorine-containing organic compound 3B coats the surface of the conductive particle 11B (the surface of the conductive part 22B) and the surface of the insulating particle 12B. In coated particle 1B, the fluorine-containing organic compound 3B is arranged on the surface of the conductive particle 11B (the surface of the conductive part 22B) and on the surface of the insulating particle 12B, and is in contact with the conductive particle 11B (conductive part 22B) and the insulating particle 12B.
[0043] In coated particle 1B, insulating particles 12B are arranged on the surface of conductive particles 11B. In coated particle 1B, insulating particles 12B are arranged on the surface of conductive portion 22B and are in contact with conductive portion 22B.
[0044] In coated particle 1B, the conductive portion 22B coats the base particle 21B and the core material 23B. Because the conductive portion 22B coats the core material 23B, coated particle 1B, conductive particle with insulating particle 2B, and conductive particle 11B have multiple protrusions 11Ba on their surfaces. The surface of the conductive portion 22B is raised by the core material 23B, forming multiple protrusions 11Ba.
[0045] Coated particle 1 and coated particle 1B differ in the presence or absence of a core material and the presence or absence of protrusions. The coated particle may or may not have protrusions on its surface.
[0046] Further details about the coated particles are described below.
[0047] In this specification, "(meth)acrylate" refers to acrylate and methacrylate. "(meth)acrylic" refers to acrylic and methacrylic. "(meth)acryloyl" refers to acryloyl and methacryloyl.
[0048] The particle size of the coated particles is preferably 0.5 μm or larger, more preferably 1.0 μm or larger, even more preferably 2.0 μm or larger, preferably 20 μm or smaller, more preferably 10 μm or smaller, and even more preferably 5.0 μm or smaller. When the particle size of the coated particles is above the lower limit and below the upper limit, when electrodes are connected using the coated particles, the contact area between the coated particles and the electrodes becomes sufficiently large, and aggregated coated particles are less likely to form when forming the conductive portion. In addition, the distance between electrodes connected via the coated particles does not become too large, and the conductive portion is less likely to peel off from the surface of the base particles.
[0049] The particle size of the coated particles is preferably the average particle size, and more preferably the number-average particle size. The particle size of the coated particles can be determined, for example, by observing 50 arbitrary coated particles with an electron microscope or optical microscope and calculating the average particle size of each coated particle, or by performing a laser diffraction particle size distribution measurement.
[0050] From the viewpoint of exhibiting the effects of the present invention more effectively, the coefficient of variation (CV value) of the particle size of the coated particles is preferably 10% or less, and more preferably 5% or less.
[0051] The coefficient of variation (CV value) mentioned above can be measured as follows.
[0052] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of the particle size of the coated particles Dn: Average particle size of coated particles
[0053] The shape of the coated particles is not particularly limited. The coated particles may be spherical, or have other shapes, such as flattened.
[0054] The above-mentioned coated particles are dispersed in a binder resin and are suitably used to obtain a resin composition.
[0055] <Base material particles> Examples of the above-mentioned base material particles include resin particles, inorganic particles excluding metal particles, organic-inorganic hybrid particles, and metal particles. The above-mentioned base material particles are preferably base material particles excluding metal particles, and more preferably resin particles, inorganic particles excluding metal particles, or organic-inorganic hybrid particles. The above-mentioned base material particles may be core-shell particles comprising a core and a shell disposed on the surface of the core. The core may be an organic core, and the shell may be an inorganic shell.
[0056] Examples of materials for the above-mentioned resin particles include polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyetheretherketone, polyethersulfone, and divinylbenzene polymers. The above-mentioned divinylbenzene polymer may also be a divinylbenzene copolymer. Examples of the above-mentioned divinylbenzene copolymer include divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylic acid ester copolymer. Since the hardness of the resin particles can be easily controlled to a suitable range, it is preferable that the material of the resin particles is a polymer obtained by polymerizing one or more polymerizable monomers having ethylenically unsaturated groups.
[0057] When the above resin particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, the polymerizable monomer having an ethylenically unsaturated group can be a non-crosslinked monomer or a crosslinked monomer.
[0058] The above non-crosslinkable monomers include styrene and styrene monomers such as α-methylstyrene; carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride; alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; and 2-hydroxyethyl (meth)acrylate and glycerol (meth)acrylate. Examples include oxygen atom-containing (meth)acrylate compounds such as polyoxyethylene (meth)acrylate and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; vinyl acid ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; unsaturated hydrocarbons such as ethylene, propylene, isoprene, and butadiene; and halogen-containing monomers such as trifluoromethyl (meth)acrylate, pentafluoroethyl (meth)acrylate, vinyl chloride, vinyl fluoride, and chlorostyrene.
[0059] The above crosslinkable monomers include tetramethylolmethane tetra(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol poly(meth)acrylate, pentaerythritol tetra(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, and (poly)ethylene glycosides. Examples include polyfunctional (meth)acrylate compounds such as poly(meth)acrylate, poly(poly)propylene glycol di(meth)acrylate, poly(poly)tetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; triallyl(iso)cyanurate, triallyl trimellitate, divinylbenzene, diallyl phthalate, diallyl acrylamide, diallyl ether, and silane-containing monomers such as γ-(meth)acryloxypropyltrimethoxysilane, trimethoxysilylstyrene, and vinyltrimethoxysilane. From the viewpoint that the resin particles maintain their shape even at the glass transition temperature of the above resin particles, the crosslinkable monomer is preferably poly(poly)ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, or dipentaerythritol poly(meth)acrylate.
[0060] The above-mentioned polymerizable monomer having an ethylenically unsaturated group can be polymerized by known methods to obtain the resin particles. Examples of such methods include suspension polymerization in the presence of a radical polymerization initiator, and polymerization by swelling the monomer together with a radical polymerization initiator using non-crosslinked seed particles.
[0061] When the above-mentioned base material particles are inorganic particles other than metal particles or organic-inorganic hybrid particles, examples of inorganic materials for forming the base material particles include silica, alumina, barium titanate, zirconia, and carbon black. It is preferable that the above-mentioned inorganic material is not a metal. Examples of particles formed from silica include particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form crosslinked polymer particles, and then firing them as necessary. Examples of organic-inorganic hybrid particles include organic-inorganic hybrid particles formed from a crosslinked alkoxysilyl polymer and an acrylic resin.
[0062] The above organic-inorganic hybrid particles are preferably core-shell type organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. From the viewpoint of effectively lowering the connection resistance between electrodes, the base particles are preferably organic-inorganic hybrid particles having an organic core and an inorganic shell disposed on the surface of the organic core.
[0063] Examples of materials for the organic core mentioned above include the resin particle material described above.
[0064] Examples of materials for the inorganic shell include the inorganic substances listed above as materials for the base particles. The material for the inorganic shell is preferably silica. The inorganic shell is preferably formed by forming a shell-like substance from a metal alkoxide on the surface of the core using a sol-gel method, and then firing the shell-like substance. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed from a silane alkoxide.
[0065] When the above-mentioned base material particles are metal particles, examples of metals that make up the metal particles include silver, copper, nickel, silicon, gold, and titanium.
[0066] The particle size of the above-mentioned base material particles is preferably 0.5 μm or more, more preferably 1.0 μm or more, preferably 10 μm or less, and more preferably 5.0 μm or less. When the particle size of the above-mentioned base material particles is above the lower limit and below the upper limit, the spacing between electrodes becomes smaller, and even if the thickness of the conductive part is increased, small conductive particles (coated particles) can be obtained. Furthermore, when forming a conductive part on the surface of the base material particles and arranging an organic compound containing fluorine, aggregation becomes less likely to occur, and aggregated conductive particles and coated particles are less likely to be formed.
[0067] The shape of the above-mentioned substrate particles is not particularly limited. The shape of the above-mentioned substrate particles may be spherical, or it may be a shape other than spherical, or it may be flattened, etc.
[0068] The particle size of the above-mentioned base material particles represents the number-average particle size. The particle size of the above-mentioned base material particles can be determined using a particle size distribution analyzer or the like. Preferably, the particle size of the base material particles can be determined by observing 50 arbitrary base material particles with an electron microscope or optical microscope and calculating the average value. When measuring the particle size of the above-mentioned base material particles in coated particles, for example, it can be measured as follows.
[0069] A resin body for inspection containing coated particles is prepared by adding and dispersing coated particles to Kulzer's "Technovit 4000" so that the coated particles have a content of 30% by weight. A cross-section of the coated particles is cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the vicinity of the center of the coated particles dispersed in the above inspection resin body. Then, using a field emission scanning electron microscope (FE-SEM) with the image magnification set to 25,000x, 50 coated particles are randomly selected and the base particles of each coated particle are observed. The particle diameter of the base particles in each coated particle is measured and their arithmetic mean is taken as the particle diameter of the base particles.
[0070] <Core material and protrusions> The coated particles preferably have protrusions on the outer surface of the conductive portion. It is preferable that there are multiple protrusions. Generally, an oxide film is often formed on the surface of an electrode that comes into contact with the coated particles. When coated particles with protrusions on their surface are used, the protrusions can effectively remove the oxide film during conductive connection. Therefore, the electrode and the coated particles can come into contact more reliably, the contact area between the coated particles and the electrode can be sufficiently large, and the connection resistance can be reduced more effectively. Furthermore, when the coated particles are dispersed in a binder resin and used as a resin composition or conductive material, the protrusions of the coated particles can more effectively remove the binder resin between the coated particles and the electrode. Therefore, the contact area between the coated particles and the electrode can be sufficiently large, and the connection resistance can be reduced more effectively.
[0071] Methods for forming protrusions on the surfaces of coated particles and conductive particles include a method in which a core material is attached to the surface of a base particle and then a conductive part is formed by electroless plating, and a method in which a conductive part is formed on the surface of a base particle by electroless plating, a core material is attached, and then a conductive part is formed by electroless plating.
[0072] Methods for attaching a core material to the surface of base particles include, for example, adding the core material to a dispersion of base particles and accumulating and attaching the core material to the surface of the base particles by van der Waals forces, for example, and adding the core material to a container containing base particles and attaching the core material to the surface of the base particles by mechanical action such as rotating the container. Among these, the method of accumulating and attaching the core material to the surface of base particles in a dispersion is preferred because it is easy to control the amount of core material to be attached.
[0073] The conductive particles may have a first conductive portion on the surface of the base particle, and a second conductive portion on the surface of the first conductive portion. In this case, a core material may be attached to the surface of the base particle, or a core material may be attached to the surface of the first conductive portion. The core material is preferably covered by the second conductive portion, and more preferably covered by both the first and second conductive portions. The conductive particles are preferably obtained by attaching a core material to the surface of the base particle, forming a first conductive portion on the surfaces of the base particle and the core material, and then forming a second conductive portion on the surface of the first conductive portion.
[0074] The materials constituting the core material mentioned above include conductive materials and non-conductive materials. Examples of conductive materials include metals, metal oxides, conductive nonmetals such as graphite, and conductive polymers. Examples of conductive polymers include polyacetylene. Examples of non-conductive materials include silica, alumina, and zirconia. From the viewpoint of increasing conductivity, the materials constituting the core material are preferably metals. From the viewpoint of increasing conductivity, the core material is preferably made of metal particles.
[0075] Examples of the above metals include gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium, and cadmium, as well as alloys composed of two or more metals, such as tin-lead alloys, tin-copper alloys, tin-silver alloys, tin-lead-silver alloys, and tungsten carbide. Among these, nickel, copper, silver, or gold are preferred. The metal constituting the core material may be the same as or different from the metal constituting the conductive part (conductive layer).
[0076] The shape of the core material described above is not particularly limited. The core material is preferably in the form of a lump. Examples of the core material include particulate lumps, aggregates formed by the aggregation of multiple fine particles, and irregularly shaped lumps.
[0077] The average height of the multiple protrusions is preferably 0.001 μm or more, more preferably 0.05 μm or more, more preferably 0.9 μm or less, and more preferably 0.2 μm or less. When the average height of the protrusions is above the lower limit and below the upper limit, the connection resistance between electrodes can be effectively reduced.
[0078] <Conductive parts> In the present invention, the conductive particles have a conductive portion on their surface. The conductive portion is arranged on the surface of the substrate particles.
[0079] The conductive part described above preferably contains a metal. The metal constituting the conductive part is not particularly limited. Examples of such metals include gold, silver, copper, tin, platinum, palladium, zinc, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium, and cadmium, as well as alloys thereof. In addition, tin-doped indium oxide (ITO) may be used as the metal. Only one of the metals may be used, or two or more may be used in combination.
[0080] From the viewpoint of further improving conductivity reliability, the conductive part preferably contains tin, nickel, palladium, copper, or gold, more preferably contains tin or nickel, and even more preferably contains nickel.
[0081] From the viewpoint of further improving conductivity reliability, it is preferable that the conductive part contains nickel as the main metal. From the viewpoint of further improving conductivity reliability, the nickel content in 100% by weight of the conductive part is preferably 15% by weight or more, more preferably 20% by weight or more, even more preferably 25% by weight or more, and particularly preferably 30% by weight or more. The nickel content in 100% by weight of the conductive part may be 100% by weight (total amount) or 90% by weight or less.
[0082] The conductive portion may be formed from a single layer. The conductive portion may be formed from multiple layers. That is, the conductive portion may have a laminated structure of two or more layers. When the conductive portion is formed from multiple layers, the metal constituting the outermost layer is preferably tin, nickel, palladium, copper, or gold, more preferably tin, nickel, palladium, or gold, and even more preferably palladium or gold. When the metal constituting the outermost layer is one of these preferred metals, the connection resistance between electrodes becomes even lower. Furthermore, when the metal constituting the outermost layer is gold, the corrosion resistance becomes even higher.
[0083] Of the total surface area of the above-mentioned substrate particles, the area covered by the conductive portion (coverage rate by the conductive portion) is preferably 80% or more, more preferably 90% or more. The upper limit of the coverage rate by the conductive portion is not particularly limited. The coverage rate by the conductive portion may be 99% or less. When the coverage rate by the conductive portion is above the lower limit and below the upper limit, the conductivity reliability can be more effectively improved when electrodes are electrically connected.
[0084] The thickness of the conductive portion is preferably 0.005 μm or more, more preferably 0.01 μm or more, preferably 1 μm or less, more preferably 0.5 μm or less, and even more preferably 0.3 μm or less. When the thickness of the conductive portion is above the lower limit and below the upper limit, the conductivity reliability is more effectively enhanced, and the conductive particles do not become too hard, allowing them to be sufficiently deformed when connecting electrodes.
[0085] When the conductive portion is formed by multiple layers, the thickness of the outermost conductive layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, preferably 0.5 μm or less, and more preferably 0.3 μm or less. When the thickness of the outermost conductive layer is above the lower limit and below the upper limit, the conductive layer of the outermost layer becomes uniform, corrosion resistance is sufficiently high, and the connection resistance between electrodes can be sufficiently low.
[0086] When the conductive portion is formed by multiple layers, the thickness of the innermost conductive layer is preferably 0.005 μm or more, more preferably 0.01 μm or more, preferably 0.5 μm or less, and more preferably 0.3 μm or less. When the thickness of the innermost conductive layer is above the lower limit and below the upper limit, corrosion resistance is sufficiently high and the connection resistance between electrodes can be sufficiently low.
[0087] The thickness of the conductive portion can be measured, for example, by observing the cross-section of the conductive particles using a transmission electron microscope (TEM).
[0088] The method for forming the conductive portion on the surface of the above-mentioned substrate particles is not particularly limited. Examples of methods for forming the conductive portion include electroless plating, electroplating, physical impact, mechanochemical reaction, physical vapor deposition or physical adsorption, and coating the surface of the substrate particles with metal powder or a paste containing metal powder and a binder. The method for forming the conductive portion is preferably electroless plating, electroplating, or physical impact. Examples of physical vapor deposition methods include vacuum deposition, ion plating, and ion sputtering. In the physical impact method, for example, a theta composer (manufactured by Tokuju Kogyo Co., Ltd.) can be used.
[0089] <Insulating particles> The coated particles according to the present invention comprise a plurality of insulating particles arranged on the surface of the conductive particle. Because the coated particles have the above configuration, when the coated particles are used to connect electrodes, short circuits between adjacent electrodes can be prevented. Specifically, when a plurality of coated particles come into contact with each other, insulating particles are present between the electrodes, thus preventing short circuits between adjacent electrodes in the lateral direction rather than between electrodes in the vertical direction. Furthermore, when connecting electrodes, insulating particles between the conductive particle and the electrode can be easily removed by applying pressure to the coated particles with the two electrodes. Moreover, if the conductive particle has a plurality of protrusions on the outer surface of the conductive part, insulating particles between the conductive particle and the electrode can be removed even more easily.
[0090] The insulating particles are preferably polymers of polymerizable compounds. The polymerizable compounds are not particularly limited. Examples of polymerizable compounds include the materials for the resin particles described above. From the viewpoint of improving conductivity reliability and insulation reliability when electrodes are electrically connected, the insulating particles are preferably resin particles. From the viewpoint of further effectively improving conductivity reliability and insulation reliability, the material of the resin particles is preferably a divinylbenzene-styrene copolymer. Furthermore, from the viewpoint of properly arranging the insulating particles on the surface of the conductive part, it is preferable that the insulating particles do not contain organic compounds containing fluorine.
[0091] Methods for arranging the insulating particles on the surface of the conductive part include chemical methods and physical or mechanical methods. Examples of chemical methods include interfacial polymerization, suspension polymerization in the presence of particles, and emulsion polymerization. Examples of physical or mechanical methods include spray drying, hybridization, electrostatic deposition, spraying, dipping, and vacuum deposition. From the viewpoint of more effectively improving insulation reliability and conductivity reliability when electrodes are electrically connected, it is preferable that the method for arranging the insulating particles on the surface of the conductive part is a physical method.
[0092] The particle size of the insulating particles can be appropriately selected depending on the particle size of the coated particles and the intended use of the coated particles. The particle size of the insulating particles is preferably 10 nm or more, more preferably 100 nm or more, even more preferably 200 nm or more, particularly preferably 300 nm or more, preferably 2000 nm or less, more preferably 1000 nm or less, even more preferably 800 nm or less, and particularly preferably 500 nm or less. If the particle size of the insulating particles is above the lower limit, when the coated particles are dispersed in the binder resin, it becomes difficult for multiple coated particles to come into contact with each other. If the particle size of the insulating particles is below the upper limit, when connecting electrodes, it becomes unnecessary to increase the pressure too much to remove insulating particles between the electrodes and conductive particles, and it also becomes unnecessary to heat to a high temperature.
[0093] The particle diameter of the insulating particles described above is preferably the average particle diameter. This average particle diameter refers to the number-average particle diameter. The particle diameter of the insulating particles is determined using a particle size distribution analyzer or the like. The particle diameter of the insulating particles is preferably determined by observing 50 arbitrary insulating particles with an electron microscope or optical microscope and calculating the average value, or by performing a laser diffraction particle size distribution measurement. When measuring the particle diameter of the insulating particles in the coated particles described above, it can be measured, for example, as follows.
[0094] Coated particles are added to Kulzer's "Technovit 4000" to a content of 30% by weight, and dispersed to create an embedded resin body for inspection containing the coated particles. An ion milling device (Hitachi High-Technologies Corporation's "IM4000") is used to cut out a cross-section of the insulating particles in the dispersed coated particles within the embedded resin body, passing through the vicinity of the center of the insulating particles. Then, using a field emission scanning electron microscope (FE-SEM) set to an image magnification of 50,000x, 50 insulating particles are randomly selected and observed. The equivalent circle diameter of the insulating particles is measured as the particle diameter, and these are arithmetically averaged to obtain the particle diameter of the insulating particles.
[0095] In the coated particles according to the present invention, two or more insulating particles with different particle sizes may be used in combination. By using two or more insulating particles with different particle sizes in combination, smaller insulating particles can fill the gaps covered by larger insulating particles, allowing for more efficient arrangement of insulating particles on the surface of conductive particles.
[0096] The coefficient of variation (CV value) of the particle size of the insulating particles is preferably 20% or less. When the coefficient of variation of the particle size of the insulating particles is below the upper limit, the thickness of the insulating particles in the resulting coated particles becomes more uniform, making it easier to apply uniform pressure during conductive connection and further reducing the connection resistance between electrodes.
[0097] The coefficient of variation (CV value) mentioned above can be measured as follows.
[0098] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of particle size of insulating particles Dn: Average particle size of insulating particles
[0099] The shape of the insulating particles is not particularly limited. The insulating particles may be spherical, or have other shapes, such as flattened shapes.
[0100] From the viewpoint of more effectively improving conductivity reliability and insulation reliability when electrodes are electrically connected, the area of the portion covered by the insulating particles (covering rate by insulating particles) out of 100% of the total surface area of the conductive portion is preferably 30% or more, more preferably 40% or more, preferably 70% or less, and more preferably 60% or less.
[0101] The coverage rate by the insulating particles can be measured, for example, by the following method: Observe the conductive particles with insulating particles attached from one direction using a scanning electron microscope (SEM), and calculate the coverage rate from the total area of the insulating particles within the circle at the outer edge of the surface of the conductive part in the observed image. Preferably, the coverage rate by the insulating particles is calculated by observing 20 conductive particles with insulating particles and averaging the measurement results of each conductive particle with insulating particles to obtain the average coverage rate.
[0102] Furthermore, the coverage rate by the insulating particles mentioned above can also be measured by mapping analysis such as EDX associated with SEM.
[0103] The coverage rate by the insulating particles can be adjusted, for example, by the amount of insulating particles added to the base particles, the mixing time, etc., so the method for adjusting the coverage rate by the insulating particles is not particularly limited.
[0104] <Fluorine-containing organic compounds> In the coated particles according to the present invention, the fluorine-containing organic compound coats at least a portion of the surface of the conductive particles with insulating particles. That is, the fluorine-containing organic compound coats at least a portion of the surface of the conductive part or at least a portion of the surface of the insulating particles. In the coated particles, the fluorine-containing organic compound (coating portion) is arranged on at least a portion of the surface of the conductive particles with insulating particles. From the viewpoint of exhibiting the effects of the present invention more effectively, it is preferable that the fluorine-containing organic compound coats at least a portion of the surface of the conductive part and at least a portion of the surface of the insulating particles. In the coated particles, it is preferable that the fluorine-containing organic compound (coating portion) is arranged on at least a portion of the surface of the conductive part and at least a portion of the surface of the insulating particles. The fluorine-containing organic compound may be a coating.
[0105] The organic compound containing fluorine may be placed between the conductive portion and the insulating particles, or it may not be placed between them. The conductive portion and the insulating particles may be in direct contact without the organic compound containing fluorine in between. From the viewpoint of exhibiting the effects of the present invention more effectively, it is preferable that the organic compound containing fluorine is placed in a region of the surface of the conductive portion where the insulating particles are not placed.
[0106] The coated particles according to the present invention have the above configuration, so that aggregation of coated particles can be suppressed. In the above coated particles, the fluorine-containing organic compound acts as a dispersant. The fluorine atoms in the fluorine-containing organic compound reduce the surface tension of the coated particles and decrease their adhesion, thereby suppressing aggregation of coated particles.
[0107] From the viewpoint of exhibiting the effects of the present invention more effectively, the area of the portion covered by the coating (covering rate by the coating) of the total surface area of the conductive particles with insulating particles is preferably 70% or more, more preferably 80% or more, even more preferably 90% or more, and most preferably 100%. The covering rate by the coating may be 100% or less, or 95% or less. From the viewpoint of exhibiting the effects of the present invention more effectively, it is preferable that the organic compound containing fluorine covers the entire surface of the conductive particles with insulating particles. From the viewpoint of exhibiting the effects of the present invention more effectively, it is preferable that the organic compound containing fluorine covers the surface of the conductive portion and the surface of the insulating particles.
[0108] The coverage rate of the above-mentioned coating can be measured by the following method. Conductive particles with insulating particles are observed from one direction using energy-dispersive X-ray spectroscopy (SEM-EDX) with a scanning electron microscope (SEM), and the coverage rate is calculated from the total area of the coating within the circle at the outer edge of the surface of the conductive part in the observed image. Preferably, the coverage rate of the above-mentioned coating is calculated as the average coverage rate obtained by observing 20 coated particles and averaging the measurement results of each coated particle.
[0109] Examples of organic compounds containing fluorine include polytetrafluoroethylene, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, perfluoroalkyl compounds, and polyfluoroalkyl compounds. Examples of perfluoroalkyl compounds include perfluoroalkyl sulfonic acid, perfluoroalkyl carboxylic acid, perfluoroalkyl phosphoric acid, and perfluoroalkylamine. Examples of polyfluoroalkyl compounds include polyfluoroalkyl sulfonic acid, polyfluoroalkyl carboxylic acid, polyfluoroalkyl phosphoric acid, and polyfluoroalkylamine.
[0110] From the viewpoint of easily coating the conductive particles with insulating particles, the fluorine-containing organic compound is preferably polyvinylidene fluoride, a perfluoroalkyl compound, or a polyfluoroalkyl compound, more preferably polyvinylidene fluoride or a perfluoroalkyl compound, and more preferably a perfluoroalkyl compound. From the viewpoint of easily coating the conductive particles with insulating particles, the fluorine-containing organic compound is particularly preferably perfluoroalkyl phosphate.
[0111] The above-mentioned fluorine-containing organic compounds can be detected by the following method: The outermost surface of the coated particles is measured using time-of-flight secondary ion mass spectrometry (TOF-SIMS), and the presence or absence of a mass spectrum originating from the fluorine-containing organic compound is observed. Examples of analytical instruments used for TOF-SIMS include the "PHI nano TOFII" manufactured by ULVAC-PHI.
[0112] In the coated particles described above, when TOF-SIMS measurement is performed, the fluoride ion intensity ratio (fluoride ion intensity / total ion intensity) in the negative ion spectrum is preferably 0.0001 or higher, more preferably 0.0003 or higher, preferably 1.0 or lower, more preferably 0.1 or lower, and even more preferably 0.01 or lower. When the above fluoride ion intensity ratio (F ion intensity / total ion intensity) is above the lower limit and below the upper limit, aggregation of the coated particles can be suppressed even more effectively. The above TOF-SIMS measurement is performed using, for example, the primary ion source 209Bi3 for measurement. ++ Measurements can be taken under conditions of an ion voltage of 25kV and an ion current of 1pA.
[0113] The method for placing the fluorine-containing organic compound on the surface of the conductive particles with insulating particles is not particularly limited. Examples of methods for placing the fluorine-containing organic compound on the surface of the conductive particles with insulating particles include dipping, spraying, and melt coating.
[0114] In 100% by weight of the above-mentioned coated particles, the content of the above-mentioned organic compound containing fluorine is preferably 0.001% by weight or more, more preferably 0.01% by weight or more, preferably 10% by weight or less, more preferably 5.0% by weight or less, even more preferably 1.0% by weight or less, particularly preferably 0.5% by weight or less, and most preferably 0.1% by weight or less. When the content of the above-mentioned organic compound containing fluorine is above the lower limit and below the upper limit, aggregation of the coated particles can be suppressed even more effectively.
[0115] (Resin composition) The resin composition according to the present invention comprises the above-described coated particles and a binder resin. The above-described coated particles are preferably dispersed in the binder resin and used as a resin composition. The above-described resin composition is preferably a conductive material, and more preferably an anisotropic conductive material. The above-described conductive material is preferably used for electrical connections between electrodes. The above-described conductive material is preferably a conductive material for circuit connections. In the above-described resin composition and conductive material, since the above-described coated particles are used, aggregation of particles in the binder resin can be suppressed. Furthermore, when electrodes are electrically connected, the conductivity reliability can be effectively increased. In addition, it is possible to prevent insulating particles from unintentionally detaching from the surface of the coated particles before conductive connection, such as by dispersing the above-described coated particles in the binder resin, and the insulation reliability between electrodes can be further increased.
[0116] The above-mentioned binder resin is not particularly limited. A known insulating resin can be used as the binder resin. The binder resin preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. Examples of the curable component include a photocurable component and a thermosetting component. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent.
[0117] Examples of the binder resins mentioned above include vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers, and elastomers. Only one type of binder resin may be used, or two or more types may be used in combination.
[0118] Examples of vinyl resins include vinyl acetate resin, acrylic resin, and styrene resin. Examples of thermoplastic resins include polyolefin resin, ethylene-vinyl acetate copolymer, and polyamide resin. Examples of curable resins include epoxy resin, urethane resin, polyimide resin, and unsaturated polyester resin. The curable resin may be a room-temperature curing resin, a thermosetting resin, a photocuring resin, or a moisture-curing resin. The curable resin may be used in combination with a curing agent. Examples of thermoplastic block copolymers include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, and hydrogenated styrene-isoprene-styrene block copolymer. Examples of elastomers include styrene-butadiene copolymer rubber and acrylonitrile-styrene block copolymer rubber.
[0119] In addition to the coated particles and the binder resin, the above resin composition may also contain various additives such as fillers, bulking agents, softeners, plasticizers, polymerization catalysts, curing catalysts, colorants, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, lubricants, antistatic agents, and flame retardants.
[0120] The method for dispersing the coated particles in the binder resin is not particularly limited and can be any conventionally known dispersion method. Examples of methods for dispersing the coated particles in the binder resin include the following: A method in which the coated particles are added to the binder resin and then mixed and dispersed using a planetary mixer or the like. A method in which the coated particles are uniformly dispersed in water or an organic dispersion medium using a homogenizer or the like, then added to the binder resin and mixed and dispersed using a planetary mixer or the like. A method in which the binder resin is diluted with water or an organic dispersion medium, then the coated particles are added and mixed and dispersed using a planetary mixer or the like.
[0121] The viscosity (η25) of the above resin composition at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, preferably 400 Pa·s or less, and more preferably 300 Pa·s or less. When the viscosity of the above resin composition at 25°C is above the lower limit and below the upper limit, the insulation reliability between electrodes can be more effectively improved, and the conductivity reliability between electrodes can be more effectively improved. The viscosity (η25) can be appropriately adjusted depending on the type and amount of the blending components.
[0122] The viscosity (η25) described above can be measured, for example, using an E-type viscometer (TVE22L manufactured by Toki Sangyo Co., Ltd.) under conditions of 25°C and 5 rpm.
[0123] When the resin composition according to the present invention is a conductive material, the conductive material can be used as a conductive paste, a conductive film, or the like. When the conductive material is a conductive film, a film without conductive particles may be laminated onto a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.
[0124] In 100% by weight of the above resin composition, the content of the binder resin is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, particularly preferably 70% by weight or more, preferably 99.99% by weight or less, and more preferably 99.9% by weight or less. When the content of the binder resin is above the lower limit and below the upper limit, conductive particles are efficiently arranged between electrodes, and the connection reliability of the connected members connected by the resin composition can be further improved.
[0125] In 100% by weight of the above resin composition, the content of the above coating particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, preferably 80% by weight or less, more preferably 60% by weight or less, even more preferably 40% by weight or less, particularly preferably 20% by weight or less, and most preferably 10% by weight or less. When the content of the above coating particles is above the lower limit and below the upper limit, the conductivity reliability and insulation reliability between electrodes can be further improved.
[0126] From the viewpoint of exhibiting the effects of the present invention more effectively, the proportion of non-aggregated coated particles out of 100% of the total number of coated particles in the binder resin is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, particularly preferably 85% or more, and most preferably 90% or more. There is no particular upper limit to the proportion of non-aggregated coated particles out of 100% of the total number of coated particles in the binder resin. The proportion of non-aggregated coated particles out of 100% of the total number of coated particles in the binder resin may be 100% (total amount).
[0127] (Connection structure) The connection structure according to the present invention comprises a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connecting portion connecting the first connection target member and the second connection target member. In the connection structure according to the present invention, the material of the connecting portion includes the above-mentioned coating particles. In the connection structure according to the present invention, the first electrode and the second electrode are electrically connected by the conductive particles.
[0128] The above-described connection structure can be obtained by the steps of placing the coating particles between the first connection target member and the second connection target member, and then performing a conductive connection by heat-compression bonding. It is preferable that the fluorine-containing organic compound and the insulating particles detach from the coating particles during the heat-compression bonding. Alternatively, the resin composition may be used instead of the coating particles.
[0129] Figure 4 is a schematic cross-sectional view showing a connecting structure using coated particles according to the first embodiment of the present invention.
[0130] The connecting structure 81 shown in Figure 4 comprises a first member to be connected 82, a second member to be connected 83, and a connecting portion 84 connecting the first member to be connected 82 and the second member to be connected 83. The material of the connecting portion 84 includes coated particles 1. The connecting portion 84 may be formed from a resin composition containing coated particles 1. Preferably, the connecting portion 84 is formed by curing a resin composition containing a plurality of coated particles 1. In Figure 4, the coated particles 1 are shown schematically for illustrative purposes. Instead of coated particles 1, coated particles 1A or coated particles 1B may be used.
[0131] The first connection target member 82 has a plurality of first electrodes 82a on its surface (upper surface). The second connection target member 83 has a plurality of second electrodes 83a on its surface (lower surface). The first electrodes 82a and the second electrodes 83a are electrically connected by one or more conductive particles 11 (omitted in Figure 4) in the coating particle 1. Therefore, the first connection target member 82 and the second connection target member 83 are electrically connected by conductive parts 22 (omitted in Figure 4) in the conductive particles 11 (omitted in Figure 4).
[0132] The method for manufacturing the above-mentioned connection structure is not particularly limited. An example of a method for manufacturing the connection structure is to place the coating particles or the resin composition between a first connection target member and a second connection target member to obtain a laminate, and then heat and pressurize the laminate. The pressure for the thermocompression bonding is preferably 40 MPa or more, more preferably 60 MPa or more, preferably 90 MPa or less, and more preferably 70 MPa or less. The temperature (heating temperature) for the thermocompression bonding is preferably 80°C or more, more preferably 100°C or more, preferably 140°C or less, and more preferably 120°C or less. When the pressure and temperature for the thermocompression bonding are above the lower limit and below the upper limit, the fluorine-containing organic compound and the insulating particles can be easily detached from the surface of the coating particles during conductive connection, further improving the conductivity reliability between electrodes.
[0133] When the laminate is heated and pressurized, the fluorine-containing organic compound and insulating particles present between the conductive particles and the first and second electrodes can be removed. For example, during heating and pressurization, the insulating particles present between the conductive particles and the first and second electrodes easily detach from the surface of the conductive particles with insulating particles. During heating and pressurization, some of the insulating particles may detach from the surface of the conductive particles with insulating particles, partially exposing the surface of the conductive portion. The exposed portion of the conductive portion comes into contact with the first and second electrodes, thereby electrically connecting the first and second electrodes via the conductive particles.
[0134] The first and second connection targets described above are not particularly limited. Specifically, the first and second connection targets include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, as well as electronic components such as resin films, printed circuit boards, flexible printed circuit boards, flexible flat cables, rigid-flexible circuit boards, glass epoxy circuit boards, and glass circuit boards. It is preferable that the first and second connection targets are electronic components.
[0135] Examples of electrodes provided on the above-mentioned connection target member include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the above-mentioned connection target member is a flexible printed circuit board, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, silver electrodes, or copper electrodes. When the above-mentioned connection target member is a glass substrate, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, or tungsten electrodes. In the case of aluminum electrodes, the electrodes may be made solely of aluminum, or they may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.
[0136] The present invention will be specifically described below with reference to examples and comparative examples. The present invention is not limited to the following examples.
[0137] The following materials were prepared.
[0138] Insulating particles: Divinylbenzene-styrene copolymer particles (resin particles, average particle size 300 nm, prepared according to Synthesis Example 1 below) Polyvinylidene fluoride particles (resin particles, average particle size 100 nm, prepared according to synthesis example 2 below)
[0139] (Synthesis Example 1) Composition A was prepared in a 1000 mL separable flask fitted with a four-neck separable cover, stirring blade, three-way stopcock, condenser, and temperature probe. Composition A contained 97 parts by weight of styrene, 3 parts by weight of divinylbenzene, 0.5 parts by weight of acid phosphooxypolyoxyethylene glycol methacrylate, and 0.1 parts by weight of 2,2'-azobis{2-[N-(2-carboxyethyl)amidino]propane}. Composition A was then weighed into distilled water to a solid content of 10% by weight, stirred at 200 rpm, and polymerization was carried out at 60°C under a nitrogen atmosphere for 24 hours. After the reaction was complete, it was freeze-dried to obtain insulating particles (divinylbenzene-styrene copolymer particles).
[0140] (Synthesis Example 2) 7.8 parts by weight of polyvinylidene fluoride resin (manufactured by Sigma-Aldrich LLC) was dissolved in 534 parts by weight of NMP (manufactured by Mitsubishi Chemical Corporation) at 80°C, and then 66 parts by weight of water was added to prepare a polyvinylidene fluoride resin solution. The obtained solution was continuously added to a particle formation tank (receiving tank) containing 600 parts by weight of water at 80°C to obtain a mixture. 7.8 parts by weight of a 10% by weight magnesium acetate aqueous solution was added to the obtained mixture to agglomerate the polyvinylidene fluoride resin particles, which were then filtered through a membrane filter and washed with water to obtain insulating particles (polyvinylidene fluoride particles).
[0141] Dispersant (coating material): Polyvinylidene fluoride (an organic compound containing fluorine, manufactured by Wako Pure Chemical Industries, Ltd. as "Polyvinylidene fluoride") Perfluoroalkyl phosphate (a fluorine-containing organic compound, "Surflon FPE-50" manufactured by AGC Seimi Chemical Co., Ltd.) Monohexyl phosphate (fluorine-free organic compound, "Monoethylhexyl Phosphate" manufactured by Tokyo Chemical Industry Co., Ltd.) Silicone compounds (fluorine-free organic compounds, such as Momentive's "TSF4700")
[0142] (Example 1) (1) Preparation of conductive particles with insulating particles Conductive particles (average particle diameter 3.0 μm, conductive portion thickness 0.15 μm) were prepared, having a conductive portion with a nickel plating layer formed on the surface of divinylbenzene resin particles (base particles).
[0143] The insulating particles (divinylbenzene-styrene copolymer particles) obtained in Synthesis Example 1 were dispersed in 30 mL of pure water under ultrasonic irradiation to obtain a 10% by weight dispersion A of insulating particles. 10 g of the above conductive particles were dispersed in 500 mL of distilled water, 1 g of the obtained dispersion A was added, and the mixture was stirred at room temperature for 8 hours. The mixture was filtered through a 10 μm mesh filter, washed with methanol, and dried to obtain conductive particles with insulating particles.
[0144] (2) Preparation of coated particles Ten g of the obtained conductive particles with insulating particles were placed in 100 g of an acetone solution in which polyvinylidene fluoride (dispersant (coating material)) was dissolved at 1% by weight, and the mixture was ultrasonically stirred at 50°C for 30 minutes. After that, the mixture was filtered through a 10 μm mesh filter, washed with methanol, and dried to obtain coated particles in which the surface of the conductive particles with insulating particles was coated with polyvinylidene fluoride.
[0145] (3) Preparation of resin composition (anisotropic conductive paste) Resin composition A (anisotropic conductive paste) was obtained by blending 7 parts by weight of the obtained coated particles, 25 parts by weight of bisphenol A type phenoxy resin, 4 parts by weight of fluorene type epoxy resin, 30 parts by weight of phenol novolac type epoxy resin, and SI-60L (manufactured by Sanshin Chemical Industry Co., Ltd.), and degassing and stirring for 1 minute. Resin composition B was obtained in the same manner as resin composition A, except that the degassing and stirring time was changed to 2 minutes. Resin composition C was obtained in the same manner as resin composition A, except that the degassing and stirring time was changed to 3 minutes.
[0146] (4) Fabrication of connecting structures A transparent glass substrate was prepared with an IZO electrode pattern (first electrode, Vickers hardness of the metal on the electrode surface of 100 Hv) with an L / S ratio of 10 μm / 10 μm formed on its upper surface. A semiconductor chip was also prepared with an Au electrode pattern (second electrode, Vickers hardness of the metal on the electrode surface of 50 Hv) with an L / S ratio of 10 μm / 10 μm formed on its lower surface.
[0147] The obtained resin composition C (anisotropic conductive paste) was coated onto the transparent glass substrate to a thickness of 30 μm to form an anisotropic conductive paste layer. Next, the semiconductor chips were stacked on the anisotropic conductive paste layer so that the electrodes faced each other. Then, while adjusting the temperature of the head so that the temperature of the anisotropic conductive paste layer reached 100°C, a pressurized heating head was placed on the top surface of the semiconductor chips, and a pressure of 60 MPa was applied to cure the anisotropic conductive paste layer at 100°C to obtain a connection structure.
[0148] (Examples 2-5 and Comparative Examples 2,3) Except for changing the composition of the coated particles as shown in Tables 1 and 2 below, coated particles, a resin composition, and a connecting structure were obtained in the same manner as in Example 1.
[0149] (Comparative Examples 1, 4) Conductive particles with insulating particles were obtained in the same manner as in Example 1, except that the composition of the conductive particles with insulating particles was changed as shown in Table 2 below. A resin composition and a connecting structure were obtained in the same manner as in Example 1, except that the obtained conductive particles with insulating particles were used as uncoated particles without being coated.
[0150] (evaluation) (1) Fluoride ion intensity ratio measured by TOF-SIMS TOF-SIMS measurements were performed on the outermost surface of the obtained coated or uncoated particles using ULVAC-PHIE's "PHInanoTOFII". From the obtained measurement results, the fluoride ion intensity ratio (fluoride ion intensity / total ionic intensity) was obtained based on the fluorine peak derived from fluorine-containing organic compounds. The TOF-SIMS measurement conditions were as follows. In Comparative Example 4, the fluoride ion intensity ratio on the surface of insulating particles in the coated particles was 0.1, and the fluoride ion intensity ratio on the surface of conductive particles was 0.
[0151] (Measurement conditions for TOF-SIMS) Primary ion: 209Bi3 ++ Ion voltage: 25kV Ion current: 1 pA (pulse current value)
[0152] (2) Percentage of uncoated or uncoated particles In the obtained resin composition C, the proportion of non-aggregated coated or uncoated particles out of 100% of the total number of coated or uncoated particles in the binder resin was measured using an optical microscope (Keyence Corporation "VH-Z450").
[0153] (3) Dispersion rate of coated or uncoated particles The dispersion rate of coated or uncoated particles was evaluated according to the following criteria by observing the proportion of uncoated or uncoated particles in resin composition A (defoaming and stirring time 1 minute), resin composition B (defoaming and stirring time 2 minutes), and resin composition C (defoaming and stirring time 3 minutes).
[0154] [Dispersion rate of coated or uncoated particles] ○○: The proportion of uncoated or uncoated particles in resin composition A, resin composition B, and resin composition C is equivalent (dispersion is completed within 1 minute). ○: The proportion of uncoated or uncoated particles in resin composition B and resin composition C is the same, but the proportion of uncoated or uncoated particles in resin composition A is less than the proportion of uncoated or uncoated particles in resin composition B and resin composition C (dispersion is completed in more than 1 minute but within 2 minutes). ×: The proportion of uncoated or uncoated particles in resin composition A and resin composition B is less than the proportion of uncoated or uncoated particles in resin composition C (dispersion takes more than 2 minutes).
[0155] (4) Insulation reliability (between adjacent electrodes in the lateral direction) In the 20 resulting connection structures, the presence or absence of leakage between adjacent electrodes was evaluated by measuring the resistance value with a tester. Insulation reliability was determined according to the following criteria.
[0156] [Criteria for determining insulation reliability] ○○: Resistance value is 10 8 The number of connection structures with an Omega value or greater is 20. ○: Resistance value is 10 8 The number of connection structures of Ω or greater is between 15 and 19. ×: Resistance value is 10 8 The number of connection structures with an Omega value or greater is 14 or less.
[0157] (5) Continuity reliability (between upper and lower electrodes) The connection resistance between the upper and lower electrodes of each of the 20 obtained connection structures was measured using the four-terminal method. Note that, based on the relationship voltage = current × resistance, the connection resistance can be determined by measuring the voltage when a constant current is flowing. Continuity reliability was judged according to the following criteria.
[0158] [Criteria for determining continuity reliability] ○○: Connection resistance is greater than 1.5Ω and less than or equal to 2.0Ω ○: Connection resistance is greater than 2.0Ω and less than or equal to 5.0Ω △: Connection resistance is greater than 5.0Ω and less than or equal to 10Ω ×: Connection resistance exceeds 10Ω
[0159] The composition and results of coated or uncoated particles are shown in Tables 1 and 2 below.
[0160] [Table 1]
[0161] [Table 2] [Explanation of symbols]
[0162] 1,1A,1B...coated particles 2, 2A, 2B... Conductive particles with insulating particles 3,3A,3B... Fluorine-containing organic compounds 11,11A,11B…Conductive particles 11Ba…Protrusion 12, 12A, 12B... Insulating particles 21,21A,21B...Base material particles 22,22A,22B…Conductive part 22AA…First conductive part 22AB...Second conductive part 23B…core substance 81…Connection Structure 82...First connection target member 82a...First electrode 83...Second connection target member 83a...Second electrode 84...Connection part
Claims
1. The device comprises conductive particles with insulating particles and an organic compound containing fluorine, The conductive particle with insulating particles comprises a conductive particle and a plurality of insulating particles arranged on the surface of the conductive particle. The conductive particles have a base particle and a conductive portion disposed on the surface of the base particle. The fluorine-containing organic compound coats at least a portion of the surface of the conductive particles with insulating particles, Coated particles wherein the fluorine-containing organic compound is polyvinylidene fluoride or perfluoroalkyl phosphate.
2. The coated particle according to claim 1, wherein the fluorine-containing organic compound coats at least a portion of the surface of the conductive portion and at least a portion of the surface of the insulating particle.
3. The coated particles according to claim 1 or 2, wherein the insulating particles are resin particles.
4. The coated particle according to claim 1 or 2, wherein the area of the portion covered by the insulating particle is 30% or more and 70% or less of the total surface area of the conductive portion.
5. A resin composition comprising coated particles according to claim 1 or 2 and a binder resin.
6. The resin composition according to claim 5, wherein the proportion of non-aggregated coated particles in the binder resin is 80% or more of the total number of coated particles in the binder resin.
7. The resin composition according to claim 5, wherein the binder resin comprises an epoxy resin.
8. A first connection target member having a first electrode on its surface, A second connection target member having a second electrode on its surface, The device comprises a connecting portion that connects the first member to be connected and the second member to be connected, The material of the connecting portion includes the coated particles described in claim 1 or 2, A connecting structure in which the first electrode and the second electrode are electrically connected by the conductive particles.
9. Conductive particles with insulating particles and polyvinylidene fluoride or perfluoroalkyl phosphate are prepared, The process includes a placement step of arranging polyvinylidene fluoride or perfluoroalkyl phosphoric acid on the surface of the conductive particles with insulating particles by dipping, spraying, or melt coating, thereby obtaining coated particles in which the polyvinylidene fluoride or perfluoroalkyl phosphoric acid covers at least a portion of the surface of the conductive particles with insulating particles. The conductive particle with insulating particles comprises a conductive particle and a plurality of insulating particles arranged on the surface of the conductive particle. A method for manufacturing coated particles, wherein the conductive particles have a base particle and a conductive portion disposed on the surface of the base particle.
Citation Information
Patent Citations
Anisotropic electrically-conductive adhesive composition
JP1995268303A
Conductive particle with insulative particle, anisotropic conductive material, and connection structure
JP2013030479A
Water repellent conductive particles, anisotropic conductive material and conductive connection structure
JP2013105537A
Conductive particle with insulative particles, manufacturing method of conductive particle with insulative particles, conductor material, and connection structure
JP2013175453A
Conductive particle with insulative particles, conductive material and connection structure
JP2015005499A